PENGARUH KREDIBILITAS BRAND AMBASSADOR SIWON CHOI TERHADAP BRAND IMAGE MIE SEDAAP : Survei Pada Followers Instagram @Miesedaapid Pada Juni 2020 - Resisca Lorensa, (2020)
Mie Sedaap is one of the most popular instant noodle products in Indonesia that has a variety of variants that are in demand by the public. In promoting the products, Mie Sedaap chose South Korean celebrity, Siwon Choi, as his brand ambassador. As a celebrity Siwon Choi is considered to have a quite good credibility in promoting a product. This study discusses the influence of Siwon Choi's credibility as a brand ambassador to the Mie Sedaap brand image. The research method used is a quantitative method with 100 respondents from Mie Sedaap followers. The theory used in this study is the source credibility theory by Hovland, Janis, and Kelley in 1953. Brand image Mie Sedaap is measured by the credibility of Siwon Choi's ambassador consisting of three elements namely trust, expertise, and attractiveness. The results of the correlation test are variable X (brand credibility of Siwon Choi ambassador) to variable Y (brand image Mie Sedaap) showing a strong correlation with a value of 0.51. The results of the coefficient of determination test are known to be 42.3%. Then the results of hypothesis testing with at count of 8.428 it can be concluded that Ho is rejected and Ha is accepted. This means that there is a strong influence between Siwon Choi's brand ambassador on the Mie Sedaap brand image.